Diurnal variations in nitrate content of red beets - Kallio, Heikki; Rousku, Raila; Salminen, Aarne (Agricultural and Food Science, 1984)
The diurnal variations in nitrate content of red beet (Beta vulgaris L. var. conditiva) roots and leaves were observed in cultivations with either no nitrogen fertilizer or with Ca(NO3)2 addition. With less nitrate in the soil the diurnal reduction of nitrate content in the afternoon was greater; on the average 55 % in the leaves and 20 % in the roots of the maximum values in the middle of August. With nitrogen fertilizing (100 kg of nitrogen/ha) the corresponding values were about 15 to 20 %. The amplitude of alteration decreased toward the end of the growing season, as the nitrate content in the leaves in particular was reduced. In our experimental conditions nitrapyrin, a nitrification inhibitor, had no effect on the nitrate content in roots or leaves.